2011
DOI: 10.1007/s11999-010-1375-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prior Salter or Chiari Osteotomy on THA with Developmental Hip Dysplasia

Abstract: Background Controversy exists regarding the outcome of THA after prior pelvic osteotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 25 publications
0
5
0
5
Order By: Relevance
“…This was a young, predominantly male trauma population with a high degree of migration and, consequently, we were unable to locate the remaining 37 patients. However, this is a common feature of orthopaedic studies [5,25], and we believe our conclusions are still valid given the congruence of current 2-year cohort demographic data with the 1-year cohort from our prior COTS study [1]. Second, 2 years of followup is still considered short-term for most orthopaedic studies.…”
Section: Discussionmentioning
confidence: 62%
“…This was a young, predominantly male trauma population with a high degree of migration and, consequently, we were unable to locate the remaining 37 patients. However, this is a common feature of orthopaedic studies [5,25], and we believe our conclusions are still valid given the congruence of current 2-year cohort demographic data with the 1-year cohort from our prior COTS study [1]. Second, 2 years of followup is still considered short-term for most orthopaedic studies.…”
Section: Discussionmentioning
confidence: 62%
“…Several surgical techniques, such as shelf graft, have been suggested for increasing the acetabular coverage in DDH patients. Failed pelvic osteotomies might have compromised the subsequent hip replacement; however, a properly performed PAO procedure or other pelvic osteotomy would contribute to the success of a later hip replacement by making the stability of the acetabular component more reliable [15,17,18], since both LCEA and ACEA postoperatively improved to the normal range in this study. How about the comparison between PAO in middle aged and hip revision in old people?…”
Section: Discussionmentioning
confidence: 76%
“…The authors concluded that previous periacetabular osteotomy did not alter surgical outcomes based on the improvement in mean Merle d'Aubigné and Postel scores. There are few other studies that compare outcomes of THA with or without other types of pelvic osteotomies (Chiari/Salters/Triple innominate) [6,7]. Therefore, prior to the study of Amanatullah et al, there was insufficient evidence to refute or support a claim that THA after prior periacetabular osteotomy yields similar results to THA without prior periacetabular osteotomy.…”
mentioning
confidence: 99%